Asosiasi Begomovirus dan Betasatelit dalam Pengendalian Penyakit Kuning melalui Pendekatan Bioteknologi - Sidik, Effi Alfiani; Laeshita, Putri (Seminar Nasional Lahan Suboptimal, 2023)
Sidik, E.A., Laeshita, P.  (2023). Association of begomoviruses and betasatellit in controlling yellow disease through a biotechnological approach. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-11 Tahun 2023, Palembang 21 Oktober 2023. (pp. 660-672).  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Begomovirus belongs to the Geminivirus family, which is the largest genus that causes disease in many plants. Begomovirus genomes are monopartite and bipartite. In recent years it has been known that monopartite and bipartite begomoviruses associate with ssDNA satellit (betasatellit). Recombination that occurs between begomoviruses and betasatellit can trigger the emergence of new species and play a role in spread. The goal of this article is to describe the association between begomoviruses and betasatellit and their role in control using biotechnological approaches. This article was studied applying a scientific literature review process. This association plays a role in triggering the emergence of symptoms in the pathogenicity process. The betasatellit region contains a single open reading frame (ORFs) (βC1 gene) as a determinant of pathogenicity. Begomoviruses and betasatellit contain ORFs that encode replication, transcription, and RNA silencing (suppressing gene silencing) activities. The existence of this association can be an alternative control that utilizes the application of RNA interference (RNAi) to control begomovirus infection. Implemented by producing transgenic plants that harbor two different RNAi hairpin intron constructs using conserved regions from the viral genome and ORFs βC1 from the betasatellit genome. The multifunctional nature of the encoded protein may be a promising alternative in the development of resistance against begomovirus infection. In the end, transgenic plants were produced with milder symptoms and less viral DNA accumulation.